2022
DOI: 10.1089/jicm.2021.0365
|View full text |Cite
|
Sign up to set email alerts
|

UC-II Undenatured Type II Collagen for Knee Joint Flexibility: A Multicenter, Randomized, Double-Blind, Placebo-Controlled Clinical Study

Abstract: Objective: Joint-related stress models have been used in the past to induce a standardized load on physical structures, allowing researchers to observe changes in perceived stress on joints as accurately as possible in healthy individuals. Previous studies support the efficacy of UC-II ® undenatured type II collagen (“undenatured collagen”) supplementation in maintaining joint health. The purpose of this study was to assess the effect of undenatured collagen on knee flex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 27 publications
1
7
0
2
Order By: Relevance
“…Similarly, joint functionality seemed to be improved in the current investigation as participants experienced reduced restrictions when squatting. Although results coming from studies in a population with a wider age range confirmed the findings [43][44][45], some investigations could not report improvements in joint pain and functionality [59,60].…”
Section: Discussionmentioning
confidence: 84%
“…Similarly, joint functionality seemed to be improved in the current investigation as participants experienced reduced restrictions when squatting. Although results coming from studies in a population with a wider age range confirmed the findings [43][44][45], some investigations could not report improvements in joint pain and functionality [59,60].…”
Section: Discussionmentioning
confidence: 84%
“…Most of the studies have evaluated the therapeutic potential of either native type II collagen [ 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 ] or hydrolyzed collagens [ 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 ] in patients with OA. However, both types of collagens have been also tested in non-osteoarthritic individuals suffering joint discomfort [ 108 , 109 , 110 , 111 , 112 , 113 ].…”
Section: Clinical Evidencementioning
confidence: 99%
“…However, in other studies no differences have been detected in serum biomarkers of joint integrity [ 89 , 108 ]. On the other hand, all studies published in non-OA individuals have reported improvements in activity-related joint discomfort and mobility [ 108 , 109 , 110 ].…”
Section: Clinical Evidencementioning
confidence: 99%
“…В большинстве исследований оценивали терапевтический потенциал нативного CII [92][93][94][95][96][97] или гидролизованного коллагена [98][99][100][101] у пациентов с ОА. Оба типа коллагена были протестированы у лиц, страдающих от дискомфорта в суставах при отсутствии ОА [102][103][104].…”
Section: механизм действия и перспективы примененияunclassified